The changing maritime industry sector in Poland : organizational field and organizational culture - Kołodziej-Durnaś, Agnieszka (Array, 2019)
This article outlines the transformations in the maritime industry sector in Poland from the perspective of organizational sociology and maritime sociology. The author attempts to analyze the main tendencies of changes occurring in the Polish maritime economy in the recent decades, and special attention is paid to the phenomena of organizational field and organizational culture. The research results are based on the analysis of documents, literature, and interviews (IDIs). Whereas the situation of the Polish maritime industry during the communist regime is briefly described as the background for further considerations, the author focuses more on the last thirty years of Polish transformation (triggered by the Round Table talks in 1989) and the fifteen years of Poland’s membership in the European Union.